Bringing The Poster Presentation Model into Classroom - Ima Widyastuti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
Making students to speak English in a large classroom becomes a big challenge for teachers. On one hand, there is no enough time for all students speak equally. On the other hand, most students are lack of confidence and English competence. As a result, the students tend to be reluctant toward the speaking activities. There have been many research under the speaking classroom activities, however, modeling professional activity into classrooms has been rare. The recent action research on a Poster Presentation model aims to make students participate in the classroom activities actively by considering their characteristics. From the individual interview and classroom observations of the 17 passive students enrolled on the four Speaking for Academic Purposes classrooms at Sarjanawiyata Tamansiswa University, Indonesia, the researchers found that the Poster Presentation model with two rules applied, i.e. no talk no grade and interrelated questions motivated the students’ participation in the speaking classroom activities. However, the Poster Presentation model did not work on those who have never experienced in natural speaking practices before. Thus, managing the classroom using the present model brings double facets among students.